The Zn- or Cu-Thionein Character of a Metallothionein Determines Its Metal Load When Synthesized in Physiological (Metal-Unsupplemented) Conditions - Mercè Capdevila; Òscar Palacios; Sílvia Atrian (Bioinorganic Chemistry and Applications)
The present work comprises the recombinant synthesis of four metallothioneins (MTs) in metal-unsupplemented cultures and the characterization of the recovered metal complexes by means of analytical and spectrometric techniques. The four MTs are two Drosophila (MtnA and MtnB), one yeast (Crs5), and one mouse (mMT1) metallothionein isoforms. These four MTs exhibit distinct metal binding preferences, from a clear Cu-thionein character to a definite Zn-thionein nature, respectively. Although in all cases, the only metal ion present in the purified complexes is Zn2+, our results highlight an inherently different behaviour of those two types of MTs, in conditions that would mimic their synthesis in physiological environments. Therefore, intrinsically different roles can be hypothesized for the constitutively-produced MT peptides in the absence of any metal overload, depending on their Zn- or Cu-thionein character.